A chemogenetic approach for treating experimental Parkinson's disease. Issue 4 (10th December 2018) - Assaf, Fadi; Schiller, Yitzhak
ABSTRACT: Background: PD is a common neurodegenerative disease primarily affecting the cortico–basal ganglia loop. Objective: To investigate whether chemogenetic‐mediated neuromodulation of various nuclei and pathways can counterbalance basal ganglia network abnormalities and improve motor disability in experimental PD. Methods: Experimental PD was induced by stereotactic injection of 6‐OHDA to the medial forebrain bundle. Designer receptors exclusively activated by designer drugs were expressed in different basal ganglia nuclei by stereotactic injections of adeno‐associated viral vectors. We compared motor performance, monitored by the open‐field and rotarod tests, after random and blinded application of either normal saline or the synthetic receptor activator, clozapine‐N‐oxide. Results: Motor performance, as measured by movement velocity, rotations, and rotarod scores, were significantly improved in PD mice by enhancing the activity of the GPe with Gq custom receptors and by reducing basal ganglia output activity, targeting the output nuclei GPi and SNr with Gi custom receptors. Conclusion: Our findings support the hypothesis that enhanced inhibitory output activity of the basal ganglia complex underlie motor signs in PD, and point to the therapeutic potential of chemogenetic based treatments in PD patients. © 2018 International Parkinson and Movement Disorder Society